Early development of the blue mussel Mytilus edulis (Linnaeus, 1758) cultured in potassium-fortified inland saline water - Dinh, H.; Fotedar, Ravi (Elsevier BV, 2016)
The low potassium concentration in inland saline water (ISW) restrains the normal development of cultured marine organisms, and thus, possesses challenges for the development of ISW aquaculture. Therefore, assessing the effects of potassium fortification in ISW on the performance of cultured marine species is an important step to determine the feasibility of their culture in ISW. The aim of this research was to investigate the effects of potassium fortification in ISW on the performance of early life stages of the blue mussel Mytilus edulis including fertilised eggs, trochophore, veliger and pediveliger larvae. These stages were reared in five different levels of potassium-fortified ISW, namely 20, 40, 60, 80 and 100% of potassium levels equivalent to the potassium level in ocean water (OW) and two controls namely, ISW at 27 ppt (ISW27) and OW at 25 ppt (OW25). The results showed that the higher levels of potassium in ISW, particularly with 100% K+ fortification (ISW100K+), invariably improved the survival and size, and reduced the developmental stage interval and deformities of blue mussel larvae. Deformities, such as faulty cell cleavage, abnormal formation of trochophore larvae, protruding mantle in veliger larvae, and indented shell margin in veliger and in pediveliger, were observed when reared in any ISW. However, rearing in ISW did not result in any deformities in settlement larvae. The number of deformities was reduced at higher K+ fortification levels, and there were no deformities in pediveliger larvae reared in ISW100K+ and in OW. These results showed that K+ fortification in ISW improves the performance of the rearing of the larval stages of the blue mussel. Statement of relevance: This study is the first attempt to culture larval stages of blue mussel Mytilus edulis in potassium-fortified inland saline water. The results have shown that that the larval development is feasible only if ISW is fortified with K+. By initiating larval culture in inland saline water, we expect better results will be reflected by adult stages.